Flawed mothering or infant signaling? The effects of deficient acoustic cues on ovine maternal response. Issue 8 (10th August 2018) - Morton, Christine L.; Hinch, Geoff; Small, Alison; McDonald, Paul G.
Abstract: The neonate distress cry, which displays a similar acoustic structure across a range of mammalian species, is highly effective in attracting, even compelling, parental care. However, if this cry is defective, as found in human and rodent neonates with poor neurobehavioral function, is the signal less enticing? Using playback recordings of a ewe's own co‐twins as stimuli in a two choice test, we compared the preference of each sheep dam for acoustic features of lamb distress calls to assess the impact of signal quality on maternal response. The results of this study indicate that lamb vocalizations with acoustic parameters reflecting poor vocal fold engagement and arousal were less likely to be preferred by their dam. Additionally, these calls were associated with delayed vocal initiation and poor infant survival behavior suggestive of subtle cognitive deficit; and support the possibility that, as in deer and rodents, ovine vocalizations within a specific fundamental frequency range may well be a trigger for optimal maternal behavior. This research has important implications for understanding failed maternal–young interactions in ungulate and other species, and for verifying standardization of infant stimuli used in maternal behavior studies.